Selective laser melting of aluminum alloys. (12th April 2017) - Aboulkhair, Nesma T.; Everitt, Nicola M.; Maskery, Ian; Ashcroft, Ian; Tuck, Chris
Abstract: Abstract : Metal additive manufacturing (AM) processes, such as selective laser melting (SLM), enable powdered metals to be formed into arbitrary three-dimensional shapes. For aluminum alloys, which are desirable in many high-value applications for their low density and good mechanical performance, SLM is regarded as challenging due to the difficulties in laser melting aluminum powders. However, a number of recent studies have demonstrated successful aluminum processing, and have gone on to explore its potential for use in advanced AM componentry. In addition to enabling the fabrication of highly complex structures, SLM produces parts with characteristically fine microstructures that yield distinct mechanical properties. Research is rapidly progressing in this field, with promising results opening up a range of possible applications across scientific and industrial sectors. This article reports on recent developments in this area of research and highlights key topics that require further attention.